1977
DOI: 10.1139/v77-425
|View full text |Cite
|
Sign up to set email alerts
|

Lifetimes of the solvated electron in liquid alcohols

Abstract: . Can. J. Chem. 55, 3058 (1977). The solvated electron, e,-, decays with first-order kinetics in pulse-irradiated aliphatic alcohols, attributed to reaction 1 : e,-+ ROH + products. It is suggested that a recent report of curved Arrhenius plots for the temperature dependence of the rate constants for reaction 1 can be ascribed to reaction of e,-with impurities.J. H. BAXENDALE et PETER WARDMAN. Can. J. Chem. 55, 3058 (1977). Dans des alcools aliphatiques irradies par pulsation, l'electron solvate e,-se decroit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…The studies in the 1970s and 1980s [19][20][21][22][23][24][25][26] showed that in dilute solutions of hydroxylic molecules (such as alcohols and water) in normal and branched alkanes, the electrons attach to pre-existing clusters S n (multimers) of these solute ( S) molecules. (2)…”
Section: Polar Solute Traps In Alkane Solventsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies in the 1970s and 1980s [19][20][21][22][23][24][25][26] showed that in dilute solutions of hydroxylic molecules (such as alcohols and water) in normal and branched alkanes, the electrons attach to pre-existing clusters S n (multimers) of these solute ( S) molecules. (2)…”
Section: Polar Solute Traps In Alkane Solventsmentioning
confidence: 99%
“…Individual alcohol and water molecules (the "monomers", n = 1) do not trap the excess electrons, and in very dilute (< 1-5 mM) alkane solutions, localized electrons still reside in solvent traps. By contrast, alcohol clusters present in more concentrated solutions [19][20][21][22][23][24][25][26] bind the electrons quite strongly. H-bonded dimers and higher multimers of hydroxylic molecules form spontaneously in alkanes by reactions (4)…”
Section: Polar Solute Traps In Alkane Solventsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Notethat 7,isustdratherthanr,beCBusethesolvation 298The Journal of Physical Chemistry, Vol. 97, No 2,. 1993 …”
mentioning
confidence: 99%